2019
DOI: 10.1017/jfm.2019.418
|View full text |Cite
|
Sign up to set email alerts
|

A framework for input–output analysis of wall-bounded shear flows

Abstract: We propose a framework to understand input-output amplification properties of nonlinear partial differential equation (PDE) models of wall-bounded shear flows, which are spatially invariant in one coordinate (e.g., streamwise-constant plane Couette flow). Our methodology is based on the notion of dissipation inequalities in control theory. In particular, we consider flows with body and other forcings, for which we study the inputto-output properties, including energy growth, worst-case disturbance amplificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…for some polynomial φ. In such cases, a duality argument (Fantuzzi, 2019) shows that our sufficient conditions for the functional inequality in Problem 1 are equivalent to those proposed by Valmorbida et al (2015Valmorbida et al ( , 2016, Ahmadi et al (2019Ahmadi et al ( , 2016Ahmadi et al ( , 2017, and Chernyavsky et al (2021).…”
Section: A Class Of Functional Inequalitiesmentioning
confidence: 82%
See 1 more Smart Citation
“…for some polynomial φ. In such cases, a duality argument (Fantuzzi, 2019) shows that our sufficient conditions for the functional inequality in Problem 1 are equivalent to those proposed by Valmorbida et al (2015Valmorbida et al ( , 2016, Ahmadi et al (2019Ahmadi et al ( , 2016Ahmadi et al ( , 2017, and Chernyavsky et al (2021).…”
Section: A Class Of Functional Inequalitiesmentioning
confidence: 82%
“…This is usually hard to do, even with computer assistance. Valmorbida et al (2015Valmorbida et al ( , 2016 and Ahmadi et al (2019Ahmadi et al ( , 2016Ahmadi et al ( , 2017 demonstrated that SOS polynomials and SDPs can be used to verify the nonnegativity of integral functionals with polynomial integrands in one or two spatial dimensions. This is achieved without discretization of the PDE state, but rather by requiring the polynomial integrand to be nonnegative pointwise after augmenting it by terms that integrate to zero.…”
Section: Introductionmentioning
confidence: 99%
“…2017; Ahmadi et al. 2019; Jovanović 2021). The input–output approach combines the linearised Navier–Stokes equations with harmonic or stochastic forcing (white or coloured in time) to qualitatively predict structural features of turbulent shear flows.…”
Section: Introductionmentioning
confidence: 99%
“…Replacing polynomial non-negativity with sum-of-squares (SOS) conditions enables one to maximize lower bounds on L * numerically by solving a hierarchy of semidefinite programs (SDPs), indexed by the degree of the Lagrange multipliers. This strategy was proposed by Valmorbida et al [16][17][18][19] and Ahmadi et al [1][2][3][4][5] in the context of stability analysis, input-output analysis, and safety verification for dynamical systems governed by polynomial PDEs, but applies equally well to constrained variational problems.…”
mentioning
confidence: 99%
“…Moreover, many popular algorithms for solving SDPs require strong duality to guarantee convergence and avoid poor numerical conditioning. Consequently, the relaxations of (1.3) proposed by [1][2][3][4][5][16][17][18][19] and [9] are equivalent from the point of view of numerical computations.…”
mentioning
confidence: 99%